2015
DOI: 10.2112/jcoastres-d-14-00104.1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition and Foraminiferal Content of Sediments for Determining Bottom Sector Environments in Guanabara Bay (Rio de Janeiro, Brazil)

Abstract: Clemente, I.M.M.M.; da Silva, F.S.; Laut, L.L.M.; Frontalini, F.; da Costa, V.L.; da Conceiçã o Rodrigues, M.A.; Pereira, E.; Bergamaschi, S.; Filho, J.G.M., and Martins, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
(77 reference statements)
2
23
0
4
Order By: Relevance
“…Siqueira et al (2006) observed the TS mean value of 6.03% in Santos estuary (São Paulo State, Brazil). Using the same TS methodology of the present study, Clemente et al (2015) recorded the mean value of 1.4% in Guanabara Bay; recorded values varying from 0.03% (IT02) to 1.73% (IT10) in Itaipu Lagoon (both in Rio de Janeiro State); and Martins et al (2016) found values of 0.04% in Bizerte Lagoon (Tunisia).…”
Section: Organic Enrichment In Surface Sediments Of Slssupporting
confidence: 59%
See 1 more Smart Citation
“…Siqueira et al (2006) observed the TS mean value of 6.03% in Santos estuary (São Paulo State, Brazil). Using the same TS methodology of the present study, Clemente et al (2015) recorded the mean value of 1.4% in Guanabara Bay; recorded values varying from 0.03% (IT02) to 1.73% (IT10) in Itaipu Lagoon (both in Rio de Janeiro State); and Martins et al (2016) found values of 0.04% in Bizerte Lagoon (Tunisia).…”
Section: Organic Enrichment In Surface Sediments Of Slssupporting
confidence: 59%
“…They allowed to identify the most impacted regions, as well as to understand the effects of the organic matter accumulation on the microbiota of coastal environments (Baptista Neto et al, 2005;Silva et al, 2008Silva et al, , 2010Silva et al, , 2011aClemente et al, 2015;Laut et al, 2016 a, b, c).…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been performed to study benthic foraminiferal distribution and ecology in the Guanabara Bay (Vilela et al, 2001(Vilela et al, a, b, 2003(Vilela et al, , 2004(Vilela et al, , 2011Fontana et al, 2006;Kfouri-Cardoso et al, 2006;Pereira et al, 2006;Figueira et al, 2007;Donnici et al, 2012;Eichler et al, 2013;Clemente et al, 2015) as well as in the sedimentary record to reconstruct paleoenvironmental evolution (e.g., Vilela et al, 2007;Baptista Neto et al, 2016). However, all the previous works in the Guanabara Bay have been based on total (living plus dead) benthic foraminiferal assemblages.…”
Section: The Main Goals Of This Studymentioning
confidence: 99%
“…Kfouri-Cardoso et al, 2006;Laut et al, 2012;Pereira et al, 2006;Figueira et al, 2007;Vilela et al, 2001Vilela et al, a, b, 2003Vilela et al, , 2004Vilela et al, , 2007Vilela et al, , 2011Donnici et al, 2012;Eichler et al, 2013;Clemente et al, 2015;Baptista Neto et al, 2016) as well as in other Brazilian (e.g., Brönnimann et al, 1981;Bonetti and Eichler, 1997;Raposo et al, 2016), and worldwide (Murray, 1991(Murray, , 2006Laut et al, 2014Laut et al, , 2016Martins et al, 2015Martins et al, a, b, 2016 transitional coastal environments. Laut et al (2012b) based on published works gave an overview of the main species that occur in the Guanabara Bay.…”
Section: The Benthic Foraminiferal Response To Toc Enrichment and Gasmentioning
confidence: 99%
“…According to Murray (1991;2006), B. elegantissima is a species that presents opportunistic behavior when the supply of organic matter increases and the oxygen concentrations drop, as observed by Vilela et al (2014), Clemente et al (2015) and Baptista-Neto et al (2017) in Guanabara Bay (Brazil).…”
Section: Composition Of Benthic Foraminifera Assemblagesmentioning
confidence: 99%